1986
DOI: 10.1590/s0034-89101986000100001
|View full text |Cite
|
Sign up to set email alerts
|

Observações sobre atividade de mosquitos Culicidae em mata primitiva da encosta no Vale do Ribeira, São Paulo, Brasil

Abstract: Relatam-se observações sobre o ciclo diário de atividade culicídea em ambiente primitivo da floresta perenifólia higrófila da encosta, do Sistema da Serra do Mar, no Vale do Ribeira, Estado de São Paulo, Brasil. Com periodicidade bimensal, e no período de dois anos, foram levadas a efeito coletas de vinte e cinco horas ininterruptas com o emprego de isca humana, bem como a utilização de armadilhas tipo Shannon operadas dentro e fora do ambiente florestal. Os resultados evidenciaram acentuada dominancia de An. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
14

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 13 publications
4
20
0
14
Order By: Relevance
“…scapularis being captured in great number of specimens at sylvatic environment (Davis 1945, Causey & Santos 1949, Rachou et al 1955, Neves 1972, Guimarães & Arlé 1984, Lourenço-de-Oliveira 1984, Forattini et al 1986a. We also found the greater number of individuals in sylvatic sites.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…scapularis being captured in great number of specimens at sylvatic environment (Davis 1945, Causey & Santos 1949, Rachou et al 1955, Neves 1972, Guimarães & Arlé 1984, Lourenço-de-Oliveira 1984, Forattini et al 1986a. We also found the greater number of individuals in sylvatic sites.…”
Section: Discussionsupporting
confidence: 70%
“…serratus was preferentially captured is sylvatic environments. Previous studies in Brazil have found the same preference (Forattini et al 1978a, 1986a,b, 1995a, Guimarães et al 1992, 1994, Lopes 1996, Ferreira 1997). However, Forattini et al (1993c) reported that Ae.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…6 As formas adultas de Kerteszia dominam entre os Culicidae em matas primitivas. 9,10,12,14,15 Em áreas de restinga, An. bellator domina sobre An.…”
Section: Abstract: Anopheles Insect Vectors Ecology Vertical Distrunclassified
“…O horário foi representado pelo perío-do das 10:00 às 11:00 do dia seguinte. A metodologia empregada obedeceu à já descrita em trabalho anterior (Forattini e col. 9,10,11 ,…”
Section: Local Characteristicsunclassified